Analysis of the Restoration of the Rasuna Said House as a Cultural Heritage Building (Agam Regency, West Sumatra) - Tela, I Nengah; Adriadi, Riki; Wongso, Jhonny (Budapest International Research and Critics University, 2021)
Efforts to preserve the Cultural Conservation are still being carried out, both by the government and by the wider community. Rasuna Said house is a cultural heritage located in Agam Regency, West Sumatra Province. Historically this building is the home of Rasuna Said who is a National Hero of Indonesia. To honor the struggle and preserve the history of this house, in 2017 the Indonesian government has designated Rasuna Said's house as a Cultural Heritage. However, the preservation of Rasuna Said's house has not been optimal, so the building of this house was found to be experiencing a lot of damage. Therefore, the researcher considers it necessary to carry out an Analysis of the Restoration of the Rasuna Said House as a Cultural Heritage Building, with the aim of knowing the level of damage and the causes of the damage. This study uses data collection methods through field observations and desk study methods, namely the method of collecting data through study and analysis of data and information using secondary data, either in the form of reports, references, or photos. The analysis carried out is data processing to produce a plan document for the restoration of the Cultural Conservation building by considering the data on measurements, descriptions, identification, photography and research that has been carried out. This study found that the level of damage to Rasuna Said's house included light damage, and the cause of the damage was material age, termites and lack of maintenance. Furthermore, the results of this study can be used as a guide in repairing and preserving Rasuna Said's house, as well as being the basis for the preparation of a building restoration plan which includes the concept of restoration and restoration recommendations. Corrective measures can be taken in terms of structural repairs and architectural restoration.